RESPON BEBERAPA VARIETAS KACANG TANAH ( Arachis hypogaeaL. ) TERHADAP PEMBERIAN PUPUK KANDANG DAN NPK - Budi Setiawan; Mbue Kata Bangun; Emmy Harso Kardhinata (Universitas Sumatera Utara, 2014)
To study respon of peanut variety againts giving manure and NPK.The Study was conductedin Tumpatan Nibung, Batangkuis, Medan at the height of land ± 25 m above sea level fromApril 2012 to July 2012 using a randomized block design of three factors ie variety(Turangga, banteng), manure ( 0 and 1,6 kg/plot ), and NPK fertilizer ( 0 g/plot, 16 g/plot, 32g/plot ). The parameters measured were plant height, number of branches, number of podscontains perplant, number of empty pods perplant, seed dry weight perplant, dry weight of100 seeds perplant sample production, production perplot.The results showed that thevarieties significantly affect plant height ( 5 MST and 7 MST ). Manure treatment obviousaffect on plant height ( 5 MST ), and the number of empty pods perplant. While significantNPK fertilizer on plant height ( 5 MST , and 7 MST ). As for the interaction between varietywith manure treatment ( V x K ) is only significant effect on plant height parameter 5 MST.Keyword : peanut,variety,manure,fertilizer NPK.